INDEPENDENT MONITORING OF EDUCATIONAL OUTCOMES AND QUALITY OF EDUCATION IN THE PRACTICE OF PEDAGOGICAL COLLEGE - Marina P. Mironova; Olga V. Burlyaeva (Высшее образование в России)
The article analyzes and summarizes the experience of pedagogical college for the development of tools for evaluation of students' knowledge. The paper dwells on the introduction of independent monitoring of educational outcomes and the education quality technology.